The effect of glocalization strategies implemented by global companies on consumer brand preference in Türkiye: The case of South Korea - Lee, Jeenee (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Küreselleşme ve yerelleşme kelimelerinin birleşmesiyle oluşan glokalleşme kavramı son yıllarda yaygın olarak kullanılmaktadır. Çalışmanın temel amacı, küresel pazarlama stratejilerinin tüketicilerin marka tercihleri üzerindeki etkisini belirlemektir. Çalışmada Türkiye'de faaliyet gösteren Güney Koreli markalar incelenmiştir. Güney Kore merkezli firmaların uyguladıkları glokal pazarlama stratejilerinin marka tercihine etkisini belirlemek amacıyla araştırmada veri toplama yöntemi olarak anket yöntemi kullanılmıştır. Araştırmadan elde edilen sonuçlar, glokalleşme stratejileri ve onun altboyutlarından duyarlılık, fiyat ve dağıtım boyutlarının tüketici tercihleri üzerinde etkili olmasına karşın, üretim, tutundurma ve çevre boyutunun tüketici tercihleri üzerinde etkili olmadığını göstermektedir.

The concept of glocalization, which is formed by combining the words 'globalization' and 'localization,' has been widely used in recent years. The purpose of this dissertation is to determine the effect of glocal marketing strategies on consumers' brand preferences. In the dissertation, South Korean brands operating in Türkiye were examined. In order to determine the effect of glocal marketing strategies implemented by South Korea-headquartered companies on consumer brand preference, the survey method was used as a data collection method in the research. According to the results obtained from the research, it was determined that the glocalization strategies in general and the sub-dimensions of glocalization strategies such as sensitivity, price, and distribution (place) were effective on consumer brand preferences, while product, promotion, and environment dimensions were not effective on consumer brand preferences.
Küresel şirketler tarafından uygulanan glokalizasyon stratejilerinin Türkiye'de tüketici marka tercihine etkisi: Güney Kore örneği
Keywords: İşletme; Business Administration